2013
DOI: 10.3109/00365521.2013.843201
|View full text |Cite
|
Sign up to set email alerts
|

Acute pancreatitis – costs for healthcare and loss of production

Abstract: OBJECTIVE. Severity of acute pancreatitis (AP) can vary from a mild to a fulminant disease with high morbidity and mortality. Cost analysis has, however, hitherto been sparse. The aim of this study was to calculate the cost of acute pancreatitis, both including hospital costs and costs due to loss of production. MATERIAL AND METHODS. All adult patients treated at Skane University Hospital, Lund, during 2009-2010, were included. A severity grading was conducted and cost analysis was performed on an individual b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
34
2
3

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 55 publications
(41 citation statements)
references
References 25 publications
2
34
2
3
Order By: Relevance
“…As for economic data, in all three OUs, costs were lower than those reported in literature, [13][14][15] with a prevalence of costs for therapeutic resources in Emergency Medicine and for diagnostic resources in the Medical Ward of Cattolica and Colleferro.…”
Section: Discussionmentioning
confidence: 41%
See 2 more Smart Citations
“…As for economic data, in all three OUs, costs were lower than those reported in literature, [13][14][15] with a prevalence of costs for therapeutic resources in Emergency Medicine and for diagnostic resources in the Medical Ward of Cattolica and Colleferro.…”
Section: Discussionmentioning
confidence: 41%
“…In all OUs, costs are lower than reported in literature (about 10,000 € per patient); [13][14][15] however, it is observed a large variability range (the overall average direct cost for patient with AP varies from € 1123.32 of Cattolica to € 1610.59 in Colleferro, and € 1825.82 in Catanzaro, where the average age is lower, but there are multiple comorbidities).…”
Section: Clinical Analysis Of Variancesmentioning
confidence: 44%
See 1 more Smart Citation
“…In Japan, Murata et al highlighted that the factors that increase admission costs of patients with acute pancreatitis are complex treatments such as necrosectomy or intensive care in case of severe pancreatitis (23). At present, due to the scarce number of studies about associated costs (21) there are few data concerning expenses arising from early or delayed cholecystectomy, and there are no studies that include the loss of work days in the costs (11). A retrospective study done in one center showed that cholecystectomy performed within the first two weeks does not increase costs as compared to late cholecystectomy (24).…”
Section: Discussionmentioning
confidence: 99%
“…Most of the expenses are due to hospitalization but the cost of the loss of work days adds an unnecessary economic burden that should be taken into account (21).…”
Section: Discussionmentioning
confidence: 99%